2017
DOI: 10.1259/bjr.20160662
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a semi-automated technique to accurately measure abdominal fat distribution using CT and MRI for clinical risk stratification

Abstract: The method described is highly reproducible and independent of rater bias. A strong interchangeable relationship exists between calculations of AFD on retrospective CT and MRI. Advances in knowledge: This is the first technique to be applicable to scans that are not performed sequentially or in a research setting. Analysis is semi-automated and results can be compared directly, regardless of imaging modality or patient position. This method has clinical utility in prospective risk stratification and will be ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 24 publications
0
12
1
Order By: Relevance
“…In our study, measurements based on MRI-DIXON were significantly higher than CT images, in terms of perianal fat thickness, AreaM and AreaH. These results were contrary to Waduud's study, which found that MRI measurements of total abdominal area and abdominal waist circumference were lower than the counterpart CT measurements 21 . But in Waduud's study, CT scan was performed in the supine position while MRI scan was performed in the prone position, and the differences were attributed to different patient positions.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…In our study, measurements based on MRI-DIXON were significantly higher than CT images, in terms of perianal fat thickness, AreaM and AreaH. These results were contrary to Waduud's study, which found that MRI measurements of total abdominal area and abdominal waist circumference were lower than the counterpart CT measurements 21 . But in Waduud's study, CT scan was performed in the supine position while MRI scan was performed in the prone position, and the differences were attributed to different patient positions.…”
Section: Discussioncontrasting
confidence: 99%
“…Strong correlations had been reported between MRI and CT images when measuring abdominal visceral fat 25 . Thereafter, several studies had verified the reliability of prospective and retrospective measurements of abdominal visceral fat using CT and MRI [18][19][20][21] . The reported results in abdominal visceral fat were consistent with what we found in peripouch fat.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations